PENERAPAN PENDIDIKAN KARAKTER MELALUI KEGIATAN EKSTRAKURIKULER PENCAK SILAT UNTUK MENINGKATKAN SELF-EFFICACY PESERTA DIDIK - Dini Hayati; Dede Idin (Institut Ummul Quro Al-Islami Bogor, 2024)
The existence of the martial art Pencak Silat is a form of local wisdom that exists in society as one of Indonesia's cultural heritage. The aim of this research is to determine the application of character education through pencak silat extracurricular activities to increase students' self-efficacy. The method used in this research is using a qualitative description method. The data analyzed is data from observations and interviews with pencak silat trainers. The results of this research show that, through the implementation of extracurricular pencak silat activities in schools, students' self-efficacy can be increased. This is demonstrated by the attitude of students who are brave in expressing opinions, have a good social spirit, are independent and tolerant